Implementasi Program Transisi Pasca Sekolah bagi Peserta Didik Tunarungu di SLB Perwari Padang - Andriani, Gaffenia; Kusumastuti, Grahita (Jurnal Penelitian Pendidikan Khusus, 2024)
In the last five years, there have been four deaf students who graduated from SLB Perwari Padang. Three of them worked, one was unemployed and no students continued to higher education. The deaf students were previously equipped with vocational skills as a post-school transition program. This study discusses the planning, implementation and evaluation of transition programs for deaf students. This study uses descriptive research with interviews and documentation as data collection techniques. The results of the study show that the implementation of the post-school transition program starting from planning, implementation and evaluation for deaf students has been going well.